P48 Exploration of variation in Management of Acutely Symptomatic Hernia – results from the MASH practice survey. (8th April 2021) - Spence, O; Proctor, V; Sayers, A; Green, S; Burns, F; Smart, N; Lee, M
Abstract: Introduction: There is minimal evidence to guide the emergency management of groin and abdominal wall hernia. The aim of this project is to understand current variations in clinical practice across the UK when managing common types of acutely symptomatic hernia. Methods: A survey of clinical practice was developed to explore the management of acutely symptomatic abdominal wall hernia (ASH) including groin (GH), umbilical (UH), and incisional hernia (IH). The survey captured respondent characteristics. It explored preferences in the management of each type of ASH, including factors related to treatment and repair strategy. Surgeons at ST3+ level with a UK practice were invited to participate through Twitter and collaborative networks. Results: In total, 144 responses were received (response rate 26%). Of these, 62 (43.1%) were Consultant Surgeons, 105 (72.9%) did not have a specialist hernia practice, and 95 (66%) did not follow specific guidelines for emergency hernia repair. There was variation in investigations used e.g. CT required for IH (91%) but less for GH (34.7%) and UH (47.2%). Open repair was preferred in all settings. For GH with ischaemic bowel 76 (52.8%) would suture repair vs. 67 (46.5%) who would use a mesh (64.2% permanent synthetic) this is similar for IH, where 59 (41%) chose suture vs. 71 (49.3%) mesh, although 61.9% favoured biologic mesh for IH. Suture repair was preferred for UH with ischaemic bowel (69.4%). Conclusion: The survey demonstrates variation in treatment of ASH. Areas which require further exploration include use of mesh and laparoscopy in the emergency setting.